Technological Model For Training Future Teachers To Resolve Pedagogical Conflicts - Majidova, Madina (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article explores the development and implementation of a technological model aimed at preparing future teachers to effectively overcome pedagogical conflicts. The proposed model integrates digital tools, simulation technologies, and interactive pedagogical methods to enhance teachers’ professional readiness for conflict management. The study highlights the importance of technology-driven approaches in teacher education and emphasizes the role of structured methodologies in fostering resilience, empathy, and problem-solving skills.